Road rage behaviours among road users in Turkey - Aktaş, Alev; Akgür, Serap Annette (Traffic Safety Research, 2023)
One of the human-caused factors that decreases traffic safety is road rage behaviors. Many of the behaviors thought to be indicative of road rage are clearly intended to be aggressive. The purpose of this study was to examine the frequency of road rage incidents experienced by road users both as victims and perpetrators. Furthermore, the goal was to investigate the impact of various and other factors on road rage behaviors in the past year. The questionnaire was completed by 633 individuals who agreed to participate in the study and reside in Istanbul, Izmir, and Ankara. All of the participants were Turkish, aged 19–76 years (M = 37.84 years, SD = 10.10); 57.3% were females, and 42.7% were males. The survey application was started with ethical approval. Using the snowball sampling method, a survey link or paper pencil forms were distributed to participants. Participants were requested to fill out the questionnaire form including information and various forms of road rage. Data were analyzed using the chi-square test and binary logistic regression analysis. Using the SPSS 28 program, all data were statistically analyzed to a significance level of p < 0.05. According to our findings, low-level road rage is most common among road users. For perpetration, this rate is 43.6%, while for victimization it is 63.2%. Overall, the results of the analysis suggest that low or high-levels of road rage perpetration and victimization may be influenced by driving a vehicle, carrying a weapon and certain demographic factors like gender, age, education level, and marital status. Numerous factors interact to facilitate road rage's emergence. In our study, various forms of road rage are significantly influenced by factors such as age, gender, education, marital status, driving a vehicle, carrying a weapon. We believe it is crucial to examine this issue from multiple perspectives. Additionally, programs for prevention and intervention that effectively reduce the prevalence of road rage incidents are critical.